Ischemic Risk in Collodion Baby: An Orthopaedic Perspective - Pauline Besonhe; Pierre-Louis Docquier (Case Reports in Orthopedics)
Collodion baby is a rare condition in which the baby is born surrounded by membranes called collodion membranes. The evolution of these membranes is towards cracking and peeling. Sometimes, retraction leads to hypoperfusion or ischemia (especially of fingers and toes). In case of acute ischemia, surgery is necessary. We report the case of a newborn in which surgery was necessary to free both fingers and toes from constrictive bands responsible for ischemia. In the absence of surgery, the constrictive bands can lead to amputation (pseudoainhum). The purpose of this case report is to expose the management and the role of an orthopaedic surgeon in the treatment of a collodion baby.